Marginalized at the center: how public narratives of suffering perpetuate perceptions of refugees’ helplessness and dependency. - Kisiara, Otieno (Migration Letters, 2015)
This paper critiques the common practice of people from refugee backgrounds giving presentations and testimonials on their displacement experiences, in college, university, and similar institutional settings. While such speaking events may be framed as opportunities to center refugee voices, this paper argues that the totality of the presentation environments, especially their focus on narratives of suffering, do in fact reinforce the marginal and powerless position with which refugees are associated. To counteract the marginalizing effects of such presentations, the paper suggests alternative ways of presentations that more meaningfully involve refugees in framing and directing such speaking events.